The The Effect of "PENTING" Education on Improving Father's Parenting Role - Yuni, Yuni; Budiastutik, Indah; Trisnawati, Elly; Marlenywati, Marlenywati (Miracle Journal of Public Health, 2024)
Stunting remains a serious health problem as it is associated with an increased risk of morbidity and mortality in children under five. Based on the 2023 Indonesian Health Survey (IHS), the prevalence of stunting in Pontianak City reached 16.7%, which still exceeds the national target. Specific interventions are needed to address this issue, especially parenting-related ones. The role of fathers in parenting is very important to improve toddlers' health status and support children's optimal growth and development. This study evaluates the effect of "PENTING" education on improving fathers' parenting role in stunting prevention. The research design was a quasi-experiment, with a sample of 30 toddlers and mothers from families at risk of stunting selected by purposive sampling. The research was conducted in Kampung KB Lembah Murai, Pontianak City. The educational intervention was conducted six times using the flip sheet media, with data measurement before and after the intervention. Data were analyzed using paired t-tests. The results showed a significant increase in the role of parenting by fathers after the intervention. This finding suggests that the "PENTING" educational program effectively strengthens fathers' role as part of stunting prevention efforts.